Noncontextual Wirings - Amaral, Barbara; Cabello, Adán; Cunha, Marcelo Terra; Aolita, Leandro [UNESP] (American Physical Society (APS), 2018)
Contextuality is a fundamental feature of quantum theory necessary for certain models of quantum computation and communication. Serious steps have therefore been taken towards a formal framework for contextuality as an operational resource. However, the main ingredient of a resource theory- A concrete, explicit form of free operations of contextuality-was still missing. Here we provide such a component by introducing noncontextual wirings: A class of contextuality-free operations with a clear operational interpretation and a friendly parametrization. We characterize them completely for general black-box measurement devices with arbitrarily many inputs and outputs. As applications, we show that the relative entropy of contextuality is a contextuality monotone and that maximally contextual boxes that serve as contextuality bits exist for a broad class of scenarios. Our results complete a unified resource-theoretic framework for contextuality and Bell nonlocality.